2008
DOI: 10.1016/j.engfracmech.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of channeling/segmentation cracks of coating: Study on the critical spacing

Abstract: Channeling/segmentation cracks may arise in the coating subjected to in-plane tensile stress. The interaction between these multiple cracks, say the effect of the spacing between two adjacent cracks on the behaviors of channels themselves and the interface around the interface corners, attracts wide interest. However, if the spacing is greater than a specific magnitude, namely the Critical Spacing (CS), there should be no interaction between such channeling/segmentation cracks. In this study, the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Wu et al (2006a) and Hu et al (2005) reported that the thermal loading would introduce periodic segmentation cracks in the coating. These segmentation cracks are further reported by Wu et al (2006b) and Wu et al (2008) to be effective on decreasing the stress concentration around the interface corner when the spacing drop into certain range. Later on, Wu et al (2007) revealed experimentally that the controllable cracking of the coating can also be developed when the specimen is subjected to in-plane tension, which is considered to be largely due to the unique pattern of the yielding stresses and residual stresses in the structure.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Wu et al (2006a) and Hu et al (2005) reported that the thermal loading would introduce periodic segmentation cracks in the coating. These segmentation cracks are further reported by Wu et al (2006b) and Wu et al (2008) to be effective on decreasing the stress concentration around the interface corner when the spacing drop into certain range. Later on, Wu et al (2007) revealed experimentally that the controllable cracking of the coating can also be developed when the specimen is subjected to in-plane tension, which is considered to be largely due to the unique pattern of the yielding stresses and residual stresses in the structure.…”
Section: Introductionmentioning
confidence: 71%
“…However, left to this vertical crack or around the other two, there is no interface crack. This means that the interface stress is relatively low therein, which may be due to the effect of the vertical cracks on relaxing the stresses (Wu et al, 2008). Fig.…”
Section: Resultsmentioning
confidence: 99%